Pengaruh Status Ekonomi, Literasi Keuangan, Pengelolaan Keuangan Terhadap Gaya Hidup Pada Generasi Z Dengan Perilaku Konsumtif - Rizal Mahendra; Mulyanto Nugroho; Ulfi Pristiana (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The purpose of this study was to determine the relationship between economic status, financial literacy, financial management on lifestyle in generation z with consumptive behavior as a moderating variable. This research uses quantitative research methods. This research also uses causal research. The population in this study were generation Z in Surabaya. Sampling in this study was carried out using purposive sampling method. The research instrument used in this research is a questionnaire made by the researcher. The measurement used in measuring the level of importance of each indicator uses a Likert scale with a range of 1 (strongly agree) to 4 (strongly disagree). The results of this study indicate that there is a significant influence of economic status, financial literacy and financial management of respondents on generation z's lifestyle. Then consumptive behavior does not moderate the influence of economic status and financial literacy on lifestyle in generation z. While consumptive behavior moderates the influence of financial management on lifestyle in generation z.